2004 Annual Report - Multilateral Investment Guarantee Agency (Washington, DC: World Bank, 2013)
Although a small agency, the Multilateral Investment Guarantee Agency (MIGA) has a broad mandate-to promote productive foreign direct investment (FDI) flows into developing countries. The Agency's results in fiscal 2004 were mixed. While the total amount of guarantees issued fell slightly, to $1.1 billion, a greater proportion of projects supported were in the poorer countries eligible for financing from the International Development Association (IDA). In membership, the Islamic Republic of Iran and Suriname joined MIGA, bringing the number of member countries to 164. Highlights for the year include: first guarantee coverage for investors from the Czech Republic and Poland; three water projects supported-two in China and one in Russia; 16 projects supported in conflict-affected countries; 65 technical assistance activities conducted in 29 countries, along with regional and global initiatives; new technical assistance work initiated in Afghanistan, China, Mali, Paraguay, South Africa and Tajikistan; the European Investor Outreach Program launched with co-funding from the Austrian government; and FDI Promotion Center launched.